Implementation of Vendor Managed Inventory (VMI) in Managing Intra Ocular Lenses (IOL) in Eye Care Organization - Sharma, Nancy (International Research Journal of Management, IT & Social Sciences, 2015)
Nowadays healthcare has a completely changed scenario as compared with the early 90âs. As more and more profit generating hospitals are coming in the industry, hospital and healthcare is no longer remains a charitable or philanthropically act. So to be remain in the market and compete within hospitals need to now focus on the different and innovative strategies in every aspect. Supply chain and operations is one of the important key of any organization which directly impact on business and revenue. Vendor Managed inventory is not a new concept but it is not efficiently utilized in service and healthcare industry as of now. Some retail and automobile industries has utilized the concept and also able to reduce the inventory cost with manageable position of stock out and over stocking position. As hospitalâs key functioning is to deal with life of patients on day to day so position of material need to be necessarily on right time and right place. This paper is based on the insight of the application of vendor managed inventory in the management of inventory for the IOL (Intra ocular lenses) that is used for the surgeries in the eye hospital. We will also study the questionnaire on the acceptability of the concept of vendor managed inventory in the hospital that will help to assess the acceptability of VMI in hospital and healthcare industry. Also a framework matrix is designed to understand the relation of VMI with the revenue earning and smoothening of operational efficiency.